Gambaran Surveilans Kesehatan Ibu dan Anak (KIA) sebagai Upaya Mengurangi Angka Kematian Ibu dan Anak di Kota Palembang - Intan Kumalasari; Neni Novalia; Abelia Junika Sari; Ahmad Bagus Wicaksono; Fatimah Azzahra; Jepanya Jepanya (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Maternal and Child Health (MCH) surveillance plays a critical role in reducing maternal and infant mortality rates in Palembang City. This study aims to provide a comprehensive overview of the implementation of MCH surveillance at the Padang Selasa Health Center in Palembang, focusing on the health conditions of mothers and children from 2022 to 2024. Using secondary data from annual and monthly reports, the study found that anemia and Chronic Energy Deficiency (KEK) in pregnant women remain significant health concerns. Furthermore, while the exclusive breastfeeding program and Vitamin A distribution showed positive outcomes, immunization coverage has declined in 2024, highlighting potential gaps in access and outreach. The study emphasizes the need for improved healthcare access, more effective nutritional education for pregnant women, and enhancements in the distribution and awareness of immunization programs to reduce maternal and child health risks.